2-Styrylchromones Prevent IL-1β-Induced Pro-Inflammatory Activation of Fibroblast-like Synoviocytes while Increasing COX-2 Expression - Ana Teresa Rufino; Mariana Lucas; Artur M. S. Silva; Daniela Ribeiro; Eduarda Fernandes (MDPI AG, 2023)
Rheumatoid arthritis (RA) is characterized by systemic immune and chronic inflammatory features, leading to the destruction of the joints. Presently, there are no effective drugs able to control synovitis and catabolism in the process of RA. 2-Styrylchromones (2-SC) are a small group of compounds characterized by the attachment of a styryl group to the chromone core that have already been associated to a wide range of biological activities, including antioxidant and anti-inflammatory activities. The present study investigated the effect of a set of six 2-SC on the interleukin-1β (IL-1β)-induced increase of nitric oxide (•NO), inducible form of nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and matrix metalloproteinase-3 (MMP-3) expression levels in human fibroblast-like synoviocytes (HFLS), pointing to the role of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation in the process. From a set of six 2-SC, presenting hydroxy and methoxy substituents, the one presenting two methoxy substituents at C-5 and C-7 of A ring and a catechol group on B ring, significantly reduced •NO production and the expression of its inducible synthase (iNOS). It also significantly reduced the catabolic MMP-3 protein expression. This 2-SC inhibited the NF-κB pathway by reversing the IL-1β - induced levels of cytoplasmatic NF-kB inhibitor alpha (IκBα), and decreasing the p65 nuclear levels, suggesting the involvement of these pathways in the observed effects. The same 2-SC significantly increased the COX-2 expression, which may indicate a negative feedback loop mechanism of action. The properties of 2-SC may be of great value in the development of new therapies with improved efficacy and selectivity towards RA, and thus deserve further exploitation and evaluation to disclose the full potential of 2-SC.